Isu Penyelarasan Flight Information Region di atas Wilayah Natuna - Asep Adang Supriyadi; Masita Dwi Mandini Manessa; Rudy Agus Gemilang Gultom (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2018)
Citizen sentiment is essential to evaluate the support toward government program. In 2015, Indonesian government proposed an acceleration program on re-alignment on Flight Information Region above Natuna area. Since then, primary of discussion is often be held as a formal or informal event. The data collected from 210 respondent, which consist of pilots, military staff, ATC staff, and academician. Furthermore, this study uses TF-IDW weighting technique to cluster the argument as positive, neutral, and negative sentiment. The result shows that most of Indonesia aviation community (75%) argue that FIR management should base on sovereignty and safety. Moreover, FIR issue under economic, national security and management shows significant positive respond (>90%) while FIR management under Singapore shows a negative response (100%). The result indicates that the aviation community supports the national program Natuna FIR re-alignment.